Impact of pollen resources drift on common bumblebees in NW Europe. (25th June 2016) - Roger, Nathalie; Moerman, Romain; Carvalheiro, Luísa Gigante; Aguirre‐Guitiérrez, Jesús; Jacquemart, Anne‐Laure; Kleijn, David; Lognay, Georges; Moquet, Laura; Quinet, Muriel; Rasmont, Pierre; Richel, Aurore; Vanderplanck, Maryse; et al.
Abstract: Several bee species are experiencing significant population declines. As bees exclusively rely on pollen for development and survival, such declines could be partly related to changes in their host plant abundance and quality. Here, we investigate whether generalist bumblebee species, with stable population trends over the past years, adapted their diets in response to changes in the distribution and chemical quality of their pollen resources. We selected five common species of bumblebee in NW Europe for which we had a precise description of their pollen diet through two time periods ('prior to 1950' and '2004–2005'). For each species, we assessed whether the shift in their pollen diet was related with the changes in the suitable area of their pollen resources. Concurrently, we evaluated whether the chemical composition of pollen resources changed over time and experimentally tested the impact of new major pollen species on the development of B. terrestris microcolonies. Only one species (i.e. B. lapidarius ) significantly included more pollen from resources whose suitable area expanded. This opportunist pattern could partly explain the expansion of B. lapidarius in Europe. Regarding the temporal variation in the chemical composition of the pollen diet, total and essential amino acid contents did not differ significantly between the two time periods while we found significant differences among plant species. This result is driven by the great diversity of resources used by bumblebee species in both periods. Our bioassay revealed that the shift to new major pollen resources allowed microcolonies to develop, bringing new evidence on the opportunist feature of bumblebee in their diets. Overall, this study shows that the response to pollen resource drift varies among closely related pollinators, and a species‐rich plant community ensures generalist species to select a nutrient‐rich pollen diet.